Persistent organic pollutants and chlorpyrifos in the cockfish Callorhinchus callorynchus (Holocephali: Callorhynchidae) from Argentine coastal waters: Influence of sex and maturity - Chierichetti, Melisa Antonela; Scenna, Lorena Beatriz; Ondarza, Paola Mariana; Giorgini, Micaela; Di Giacomo, Edgardo Ernesto; Miglioranza, Karina Silvia Beatriz (Science of The Total Environment)
Organic contaminants are of great environmental concern due to their negative impacts on coastal ecosystems, especially on highly vulnerable species as chondrichthyans. Accumulation of organochlorine pesticides (OCPs), polychlorinated biphenyls (PCBs), polybrominated diphenyl ethers (PBDEs) and chlorpyrifos was assessed in muscle, gonads, and liver of the cockfish Callorhinchus callorynchus for both sexes and maturity stages. This species has a wide distribution in South Atlantic Ocean and it is an important resource for coastal Argentine fisheries. Pollutants were quantified by gas chromatography with electron capture detector and the distribution pattern found in C. callorynchus was the following: (∑OCPs+chlorpyrifos) > ∑PCBs>∑PBDEs. Endosulfan was predominant among OCP groups, penta-CBs and hexaCBs among PCBs and BDE 47, 66, 99, and 100 in PBDE group. The highest levels were found in liver followed by muscle and gonads. The highest percentage of lipids was also observed in the liver. Moreover, the concentrations of ∑OCPs and ∑PCBs in C. callorynchus liver varied with maturity stage, and ∑OCPs also with sexes. Females presented higher values than males, and mature individuals showed higher concentrations than immature ones, according with biological parameters such as age, sex, maturity stage, metabolic and redistribution processes and habitat use influence. These results indicate that C. callorynchus reflects a historical and recent contamination in their tissues, and therefore, especially females, becomes as a good biomonitor of these pollutants in the marine environment. To our knowledge, this work represents one of the few investigations on the occurrence of POPs and chlorpyrifos in chondrichtyans from South Atlantic Ocean; therefore more research is mandatory for an adequate management and conservation of existing fisheries and aquatic resources. Fil: Chierichetti, Melisa Antonela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. ...